Bacterial Infection Associated with Respiratory Cystic Fibrosis in Al-Hilla City - Rawaa M. Mohammed (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Back ground: Autosomal genetic diseases throughout North America are propagated by CF, which is seen in 1 out of 2000 Caucasians. This sickness can in most cases be undetected and is nongendered with a global impact and targets all ages. By the impaired mucocilliary clearance in the trachea and bronchi, and the inability to maintain innate defenses, acute and recurrent bacterial infections, airways obstruction and inflammation and chronic bacterial infections are aggravated. Aim of study: The study aims to isolate and identify bacterial species related to respiratory fibrosis and to do the susceptibility test to those species. Methodology: The study was carried out between January-July 2024, 80 cystic fibrosis patients admitted in Mirjan hospital, 50 came outpatients clinic and 30 found sleeping in the hospital (Eighteen in the respiratory lobbies and 12 in the intensive care unit (ICU)), patient age range between 20-80 years old, and include both gender, 28 females and 52 male.es). By using sterile labeled machines every patient provide sputum that was transported to laboratory directly after collection and stored in 4 C temperatures until culture. All samples of sputum were cultivated for twenty-four hours at 37 degrees Celsius in an incubator utilizing MAConkey and Blood agars. Thereafter, samples were streaked unto several selective and differential media where bacterial colonies matured to reveal their biochemical characteristic after 24hrs of incubation. Results: The current study's results indicated that age has an impact on microbial CF infection. Of the 80 total patients, 9 sample in the age group of 20–30 years had a percentage of 11.25%, while 11 patients in the age group of 31–40 years had a percentage of 13.75%, 16 patients in the age group of 41–50 years had a percentage of 16.25%, and 17 patients in the age group of 51–60 years had a percentage of 21.25%. The current study confirmed that infection rates increase with age. In terms of gender, the study show that males are more likely than females to get infections. with 52 males in the (65%) percentage and 28 females in the (35%), Ten patients are in the 71–80 age range, and twenty patients are in the 61–70 age group. Conclusion: The kind of bacterial strain, the patient's immunological condition, and the usage of contaminated medical equipments are some of the factors that affect transmission. During treatment, all CF patients colonized or infected with the primary pathogens discussed in this article must be kept in a single room to prevent nosocomial dissemination of the microorganism to other patients. Despite the intricacy of the epidemiology of bacterial infections in CF patients, the average lifespan of these individuals continues to increase.